Pendampingan Radiografer dalam Quality Control Pelaksanaan Repeat Analysis di Instalasi Radiologi - Siti Rosidah; Indah Sulistyowati (Universitas Pahlawan Tuanku Tambusai, 2026)
Repeat analysis is a quality assurance program regarding medical imaging to determine the cause of image repetition, as a reference for radiographers, department workflows, and ultimately reduce patient dose (Atkinson et al, 2020). Based on the decision (Minister of Health Number 129/Menkes/SK/II/2008), the standard for radiographic image rejection is ≤ 2%. Most radiology installations have not implemented a comprehensive repeat analysis program so that the repeat rate has increased or decreased. The service team wants to provide assistance regarding the calculation, analysis and evaluation of repeat analysis and provide motivation to partners to routinely carry out quality assurance programs through socialization and mentoring to maintain service quality. The repeat analysis quality assurance program already exists but has not been routinely evaluated, March-May 2025 although still within normal limits (≤ 2%), the repeat rate increased from 0.8%, 1.17% and 1.23%, an average of 1.07%. The factors causing repeats were cut by 80%, movement by 13.3% and position by 6.67%. To minimize this, it is best to carry out periodic analysis and evaluation and look for causes and solutions.